2013
DOI: 10.1088/0268-1242/28/10/105015
|View full text |Cite
|
Sign up to set email alerts
|

Non-local exchange correlation functionals impact on the structural, electronic and optical properties of III–V arsenides

Abstract: Exchange correlation (XC) energy functionals play a vital role in the efficiency of density functional theory (DFT) calculations, more soundly in the calculation of fundamental electronic energy bandgap. In the present DFT study of III-arsenides, we investigate the implications of XC-energy functional and corresponding potential on the structural, electronic and optical properties of XAs (X = B, Al, Ga, In). Firstly we report and discuss the optimized structural lattice parameters and the band gap calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 61 publications
4
16
0
2
Order By: Relevance
“…It is clear that for these two crystals the highest and the lowest energy level bands are positioned at Γ, which exhibit direct band gaps of 2.461 and 3.16 eV for Li 2 CdGeS 4 and Li 2 CdSnS 4 compounds respectively. The computed band gaps are smaller than the experimental values (3.10 for Li 2 CdGeS 4 and 3.26 for Li 2 CdSnS 4 ), but giving close agreement to the experimental measurements of diffuse-reflectance spectroscopy [1] compared to the previous theoretical work of Li et al [11]. Furthermore, in the present investigations, the band gap nature of Li 2 CdGeS 4 is found direct compared to Li et al [11], where it was found indirect.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…It is clear that for these two crystals the highest and the lowest energy level bands are positioned at Γ, which exhibit direct band gaps of 2.461 and 3.16 eV for Li 2 CdGeS 4 and Li 2 CdSnS 4 compounds respectively. The computed band gaps are smaller than the experimental values (3.10 for Li 2 CdGeS 4 and 3.26 for Li 2 CdSnS 4 ), but giving close agreement to the experimental measurements of diffuse-reflectance spectroscopy [1] compared to the previous theoretical work of Li et al [11]. Furthermore, in the present investigations, the band gap nature of Li 2 CdGeS 4 is found direct compared to Li et al [11], where it was found indirect.…”
Section: Resultssupporting
confidence: 88%
“…The modified Becke-Johnson (mBJ) [10,11] potential is used for the exchange and correlation effects. The Li 2 CdGeS 4 and Li 2 CdSnS 4 compounds have an orthorhombic symmetry.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LDA calculation of Anua and his group 13 17 reported the band gap values of 1.1 and 1.60 eV for their LDA and GW calculations, respectively. A first principle, self-consistent, orthogonalized-plane wave calculation (SCOPW) of Skutel 9 yielded an indirect band gap of 1.6 eV from U to X.…”
Section: Introductionmentioning
confidence: 99%
“…При этом в теоретических ра-ботах [2,[18][19][20][21][22] по d-зонам основное внимание уделе-но не природе этих структур, а проблеме завышения положения среднего уровня d-зон на ∼ 3−4 эВ в при-ближении локальной плотности (LDA) и обобщенного градиентного приближения (GGA). Попытка теорети-ческого описания оптических свойств кристалла InAs без учета экситонных эффектов в области энергий > 10 эВ представлена в работе [23]. В области энергий 10−17 эВ теоретические спектры отражения в [23] в 2−3 раза интенсивнее экспериментальных [13] и со-держат множество (∼ 6−7) очень слабых максимумов и ступенек.…”
Section: Introductionunclassified